Parental Involvement in Online Learning During the Covid-19 Pandemic - Yunulius, Yunulius; Lydia Lestari; Engla Wita (PT. Mifandi Mandiri Digital, 2022)
The Covid-19 pandemic that occurred in various regions, resulted in changes in aspects of life, one of which was education, and parental involvement in online learning which made parents closer and more involved in assisting children to study at home. The purpose of this study was to measure the role of parents during their children's learning activities at home and to measure the level of achievement of learning outcomes during the pandemic. The results of this study parents are involved in learning and have difficulty using the internet, parents are less able to guide and understand the material manually so they cannot be optimal in teaching children and there are no cellphones so with the cooperation of parents and teachers to encourage, motivate and provide innovations/facilities in guiding and directing children so that they are not bored and even stressed in learning during the pandemic to achieve student achievement results.